Production Administration Process In Metal Company - Melda markos (Neo Journal of economy and social humanities, 2022)
The purpose of this study is to find out how the production administration process is carried out by metal metal companies, to find out problems or obstacles in the production administration process at metal metal companies, to find solutions and overcome problems or obstacles in the production administration process at metal metal companies. The research methodology used is descriptive qualitative which aims to describe the conditions and analyze the production administration process in metal metal companies. This research requires data related to the author's study which is sourced from literature studies, field studies, documentation techniques. The results of the research regarding the production administration process at metal metal companies, namely the Production Administration Process at metal metal companies, are inputting daily production report data, inputting non-standard goods data, inputting machine damage data and archiving production documents. The obstacles that often occur are incomplete product number writing, error codes from the quality control section that are not in accordance with procedures, and incomplete engine number writing. Efforts to overcome the obstacles that often occur in the production administration process at metal metal companies, provide solutions by ensuring the product number is in accordance with SAP (System Application and Product In Data Processing), opening quality control production reports and updating machine numbers regularly.